Cyclometalated Iridium(III) Complexes as Mitochondria‐targeting Photosensitizers against Cisplatin‐resistant Cells. (4th March 2021) - Xiong, Kai; Zhou, Ying; Lin, Xinlin; Kou, Junfeng; Lin, Mingwei; Guan, Ruilin; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract: Four iridium (III) complexes Ir1‐Ir4 were synthesized and characterized. Possessing high singlet oxygen production ability and specific mitochondria‐localization, Ir1 was developed as a mitochondria‐targeting photosensitizer. Ir1 exhibited strong phototoxicity against cancer cell line A549 and its corresponding cisplatin‐resistant one A549R. In contrast, Ir1 showed low cytotoxicity toward normal cell HLF. This selectivity resulted from the different uptake amount. With 405 nm irradiation, Ir1 induced mitochondria‐mediated cell death in A549R cells, achieving the overcome of drug‐resistant. Abstract : A cyclometalated Ir(III) complex was developed as a mitochondria‐targeting photodynamic agent. Upon 405 nm irradiation, Ir(III) complex induced mitochondria membrane potential damage and eventually cell death through the generation of singlet oxygen.